La falta de cumplimiento de una de las partes de la resolución expedida en la audiencia de mediación sobre el régimen de visitas, vulnera el principio de interés superior del niño. Cantón Guaranda provincia Bolívar. - Sánchez Villagómez, Luis Alejandro (2024)
The present investigation has as a general objective to analyze from the legal and doctrinal perspective the violation of the principle of the best interest of the child when there is a breach of the visitation regime that is established through a mediation hearing, which generates a violation of the rights that attend children and adolescents to maintain interpersonal and emotional relationships with one of their parents who does not live in their home on a daily basis, from the Ecuadorian legal system visits by parents to their children are guaranteed, in such a way that they must develop without any type of obstruction, since they are aimed precisely at satisfying that affective need of children and adolescents who do not have permanent contact with one of their parents. The present investigation is developed under a mixed approach in which the qualitative and quantitative method is applied in order to establish the precise data referring to the problems raised in daily life, among the research techniques the survey and interview were applied, which helped to compile real data of the investigated problem, as a result of the investigation it is determined that non-compliance with the visiting regime established within a mediation center violates the principle of the best interest of the child, which guarantees the exercise of each of the rights that they assist the children. 3 Keywords: Coexistence. Family, Best interests of the child, Mediation. Visiting schedule.